Molecular heterogeneity in adjacent cells in triple-negative breast cancer - Huebschman ML (Dove Medical Press, 2015)
Michael L Huebschman,1 Nancy L Lane,1 Huaying Liu,1 Venetia R Sarode,2 Judith L Devlin,1 Eugene P Frenkel1,3 1Harold C Simmons Comprehensive Cancer Center, 2Department of Pathology, 3Division of Hematology-Medical Oncology, Department of Internal Medicine, UT Southwestern Medical Center, Dallas, TX, USA Purpose: This study interrogates the molecular status of individual cells in patients with triple-negative breast cancers and explores the molecular identification and characterization of these tumors to consider the exploitation of a potential-targeted therapeutic approach. Patients and methods: Hyperspectral immunologic cell by cell analysis was applied to touch imprint smears obtained from fresh tumors of breast cancer patients. Results: Cell by cell analysis confirms significant intratumoral molecular heterogeneity in cancer markers with differences from polymerase chain reaction marker reporting. The individual cell heterogeneity was recognized in adjacent cells examined with panels of ten molecular markers in each single cell and included some markers that are considered to express “stem-cell” character. In addition, heterogeneity did not relate either to the size or stage of the primary tumor or to the site from within the cancer. Conclusion: There is a very significant molecular heterogeneity when “adjacent cells” are examined in triple-negative breast cancer, thereby making a successful targeted approach unlikely. In addition, it is not reasonable to consider that these changes will provide an answer to tumor dormancy. Keywords: hyperspectral, cancer stem cells, CSC, CD44, CD24, ALDH1, uPAR, CD133, Her-2